Integration of Arduino Media in Science Learning to Improve the Technology Literacy of Madrasah Ibtidaiyah Students - Erwinsyah, Alfian; Bakari, Aljunaid; Ahmad, Hasdin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the effectiveness of Arduino integration in science learning to improve the technological literacy of Madrasah Ibtidaiyah (MI) students and formulate practical recommendations for teachers and policy makers. The study used a pre-test-post-test one group design with a sample of 23 students. Descriptive statistical analysis, paired sample t-test, and Shapiro-Wilk normality test were applied to measure the improvement of technological literacy. Learning is designed in six phases. Instruments include technology literacy tests (pretest-posttest), project assessment rubrics, and observation sheets. The results of the study were that there was a significant increase in technology literacy skills with an average difference of 24.95 points. The paired t-test confirmed a significant difference (t = -73,113, p < 0.001), supported by a narrow confidence interval (-25,664 to -24,249) and a strong correlation between scores (r = 0.905, p < 0.001). The six-phase model has been shown to be effective in improving programming, problem-solving, and collaboration skills. The integration of Arduino in science learning significantly increases technology literacy in students at Madrasah Ibtidaiyah. Recommendations include preparation of teacher training and curriculum policies that encourage the integration of ICT in madrasah science learning.